EXPLORING THE DRIVERS OF CHANGE READINESS AND COMMITMET THROUGH THEMATIC ANALYSIS - Wirda Savitri; Aurik Gustomo (CV. Radja Publika, 2025)
As the world and industry changes, companies can either resist the change or follow and transform themselves to survive. Change is difficult. Majority of companies failed to conduct change, and one of the main factors that determines change are the individuals in the organization. The same is occurring in The Company where their transformation facing threatening challenges and delay. A root cause analysis found that change readiness and change commitment may influence the issue in hand. Therefore, drivers of change readiness and change commitment were identified based on extensive literature review of 25 literatures to identify 4 main drivers which are: Transformational Leadership, Perceived Organizational Support, High-Performing HRM Practice, and Belief in Self-Efficacy. The research conducted qualitative approach through interview and thematic analysis. The interviews were conducted to 6 interviewees who are involved in the transformation of The Company. Thematic analysis was conducted in accordance with each of the change readiness and change commitment drivers by utilizing ChatGPT. The result from the interview and analysis elaborated that The Company weaknesses could be identified in its human resources management practices where it is deemed as lacking according to the interviewees’ answer. From the analysis, solutions were identified and elaborated.